2015
DOI: 10.1007/s11695-015-1663-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Reproductive Function in Male Obesity Before and After Bariatric Surgery—A Comprehensive Review

Abstract: Young males represent one of the populations with the steepest increases in the incidence of obesity. They are also prone to significant derangements in sexual health and fertility. Despite a growing number of reports about female reproductive health, in the setting of bariatric surgery, males have received much less attention. In the current review of reproductive abnormalities in severe obese males before and after bariatric surgery, erectile function, hypothalamic-pituitary-gonadal axis status, sex hormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 147 publications
1
10
0
Order By: Relevance
“…In the case of men, research proved impaired sexual function in overweight and obese subjects [3]. As a result of the presence of central obesity, hypertension, diabetes, insulin resistance and hormone disorders, this population is more prone to experience erectile dysfunction (ED) [4, 5]. Erectile dysfunction is defined as the inability to achieve and maintain an erection sufficient to permit satisfactory sexual intercourse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of men, research proved impaired sexual function in overweight and obese subjects [3]. As a result of the presence of central obesity, hypertension, diabetes, insulin resistance and hormone disorders, this population is more prone to experience erectile dysfunction (ED) [4, 5]. Erectile dysfunction is defined as the inability to achieve and maintain an erection sufficient to permit satisfactory sexual intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…The procedures are equally effective in the case of weight loss, but LRYGB seems to be more effective in resolving comorbidities [7, 8]. The weight loss after bariatric surgery leads to the normalization of hormone levels and resolution of comorbidities, especially hypertension and diabetes [5]. In the majority of patients, there is a reduction of antihypertensive and diabetic drug use in the post-operative period [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that morbid obesity is associated with sub-fertility [16,17,18,19], reduced semen quality [19,20,21,22], impaired sperm acrosome reaction [23], and sperm fatty acid composition and functions [24,25]. In particular, a large population study performed in men ( n = 4,860), classified according to their BMI (underweight: n = 45, normal weight: n = 1,330, overweight: n = 2,493, obese: n = 926, and morbidly obese: n = 57), has shown that at both extremes of BMI (underweight and morbidly obese subjects), semen parameters were significantly worse and associated with lower sperm epididymal maturation compared to the other BMI classes [22].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a public health concern with increased prevalence in the past two decades ( 1 ). The highest peak is in women and men aged between 20 and 40 years ( 2 ). In adults aged 20 years and above, it is defined as body mass index (BMI) equal to or greater than 30 kg/m 2 ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can even affect reproductive functions in both sexes and lead to pregnancy/perinatal or offspring adverse effects ( 1 ). In men, it may cause oligozoospermia and asthenozoospermia ( 1 ), erectile dysfunction ( 2 ) and subfertility ( 6 ). The estimated annual medical costs of illness pertinent to adult obesity exceed 200 US billion ( 5 ).…”
Section: Introductionmentioning
confidence: 99%